Case report: A case report and literature review on the efficacy of high-dose aumolertinib combined intrathecal pemetrexed by Ommaya reservoir for EGFR-mutated NSCLC with leptomeningeal metastasis as the initial symptoms - Zhong, Maoxi; Zhou, Li; Guo, Jing; Chen, Chuan; Wang, Wei; Huang, Xiaoping; Liu, Yi (Frontiers in Oncology, 2025)
Leptomeningeal metastasis (LM) is a significant complication of advanced non-small cell lung cancer (NSCLC), occurring in only 3-5% of patients and exceedingly rare in newly diagnosed NSCLC patients. This also indicates that the tumor is highly malignant and aggressive, which brings great challenges to treatment. Here we present a case report of an EGFR-mutated NSCLC patient who presented with LM as the primary clinical manifestation, and review the latest advances in existing studies on LM-related treatment. The patient underwent multiple cycles of high-dose aumolertinib in combination with intrathecal pemetrexed administered via Ommaya reservoir. As of the submission date, the patient achieved significant remission and a LM Progression-Free Survival (PFS) exceeding 20 months. This case highlights the positive impact of high-dose aumolertinib combined with intrathecal pemetrexed on NSCLC patients presenting with severe meningeal symptoms as the initial manifestation, offering a viable therapeutic approach for managing severe meningeal symptoms associated with LM, such as headache, nausea, neck stiffness, and vomiting.